Encyclopedia of Life Sciences 2007
DOI: 10.1002/9780470015902.a0000335
|View full text |Cite
|
Sign up to set email alerts
|

Red Algae

Abstract: Red algae are ancient aquatic plants with simple organization, noteworthy colour variation, vast morphological plasticity, challenging taxonomy and most extant species (about 6000 worldwide) are marine. They include species with complex life cycles, significant ecological importance and extensive economical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Carrageenan is extracted from red seaweeds. Several groups of red algae show superior concentrations of one particular group and thus are known as carrageenophytes (carrageenan-producers), with most families belonging to the Gigartinales [ 195 , 196 ]. Several commercial red seaweed species supply a sub-family of carrageenan extracts.…”
Section: Seaweeds Biodiversity and Potential To Exploitationmentioning
confidence: 99%
“…Carrageenan is extracted from red seaweeds. Several groups of red algae show superior concentrations of one particular group and thus are known as carrageenophytes (carrageenan-producers), with most families belonging to the Gigartinales [ 195 , 196 ]. Several commercial red seaweed species supply a sub-family of carrageenan extracts.…”
Section: Seaweeds Biodiversity and Potential To Exploitationmentioning
confidence: 99%
“…Besides the peaks of the type I β cellulose, the presence of a crystallographic plane in 2θ ¼ 17.65 with higher intensity was also noticed for the fabrics modified with PAni Leucoemeraldine base and Pernigraniline base. The presence of this peak with higher intensity is attributed to the alteration of cellulose from type I to type III, which took place due to the presence of amines, [67] such as phenylhydrazine and nitric acid, used to the treatment of the fabrics.…”
Section: Macromolecular Symposiamentioning
confidence: 99%
“…Due to the impacts associated with nuisance algal blooms on the fishery, water quality, and human, rapid assessment is inevitable. Red algae are a widespread group of uni-to-multicellular aquatic photoautotrophs, of which about 98% are marine, and 2% are freshwater (Deluquei & Lopez-Bailtista, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, studies on red algae have been reported interchangeably (seaweeds and algae) in marine or coastal ecology (Msuya & Neori, 2002;Buriyo et al, 2004;Msuya, Kyewalyanga, & Salum, 2006;Troell et al, 2011). The social-economic potentials of the industry have led Tanzania to be among the group of leading carrageenan-producing (food derived from red algae or seaweeds) in the tropical area along with the Philippines and Indonesia (Deluquei & Lopez-Bailtista, 2007).…”
Section: Introductionmentioning
confidence: 99%